Quality of Sleep and its Impact on the Academic Performance of Undergraduate Medical Students - Sah, Satish Kumar; Singh, Neeti; Pandey, Srijana; Sherpa Lama, Ang Tshering; Panta, Prem Prasad; Shrestha, Ayasha; Shah, Sachin; Bhattarai, Pawan; Ray, Raju; Chettri, Mahesh Singh (Nepalese Medical Journal, 2024)
Introduction: Good quality sleep and adequate amount of sleep are important in order to have better cognitive performance, academic performance and avoid health problems and psychiatric disorders. Sleep disturbance is a distressing and disabling condition that affects many people, and can affect on quality of work and education of students. Thus the aim of the study to assess the factors that contributes to the quality of sleep and its impact on academic performance.Materials and methods: This cross-sectional study was conducted among undergraduate medical students of KIST Medical College and Teaching Hospital from May to June 2024 after taking ethical clearance from KIST Medical College and Teaching Hospital- Institutional Review Committee before collecting data from participants. Subjects were recruited by Non-Probability sampling technique from students of first, second, third and fourth years and were asked to fill the self-reported questionnaires, using Pittsburgh Sleep Quality Index. Descriptive statistical analysis was done using Statistical Software for Social Sciences version 16. Results: Out of 280 medical students, 83(29.6%) have poor sleep quality with prevalence among male and female students as 44 (53.01%) and 39(46.99%) respectively. Age, year of study and exam result was found to be statistically significant with p value less than 0.05. Conclusions: This poor sleep quality is directly and indirectly affecting physical and social health as well as the academic performance of the students. Awareness programs concerning the effect of distorted sleep cycle are suggested to be conducted.